2018
DOI: 10.13005/bbra/2637
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant Activity of Wild Pomegranate Collected from Patnitop, Jammu & Kashmir

Abstract: Wild pomegranate is an ancient fruit with known medicinal and curative properties, attributing to overall positive health. The present study focuses on phytochemical analysis and the antioxidant potential of the fruits (red and green), leaves and flowers of wild pomegranate. High amount of carbohydrates and proteins were observed in red fruits, followed by green fruit, while they were low in flowers and leaves. However, leaves possessed higher amounts of phenolics and tannins as compared to other tissues and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Bustamante et al [ 42 ] reported that pomegranate peels extract of Wonderful cultivar from Chile exhibited antioxidant activity of 99.4 μg trolox equivalent (TE)/g under ideal conditions of extraction. Kaur et al [ 43 ] mentioned that the highest antioxidant activity assessed by DPPH method was recorded in red fruits (IC 50 = 70.33 μg/mL) while the lowest in leaves (IC 50 = 120.78 μg/mL). Also, the maximum antioxidant activity by ferric reducing power assay was in red fruits while the lowest antioxidant phenomenon was recorded in leaves (310.99 ± 0.98 μmol Fe 2+ /g and 69.99 ± 0.45 μmol Fe 2+ /g dry matter, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Bustamante et al [ 42 ] reported that pomegranate peels extract of Wonderful cultivar from Chile exhibited antioxidant activity of 99.4 μg trolox equivalent (TE)/g under ideal conditions of extraction. Kaur et al [ 43 ] mentioned that the highest antioxidant activity assessed by DPPH method was recorded in red fruits (IC 50 = 70.33 μg/mL) while the lowest in leaves (IC 50 = 120.78 μg/mL). Also, the maximum antioxidant activity by ferric reducing power assay was in red fruits while the lowest antioxidant phenomenon was recorded in leaves (310.99 ± 0.98 μmol Fe 2+ /g and 69.99 ± 0.45 μmol Fe 2+ /g dry matter, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Anardana is also used as a source of livelihood by the locals (Mushtaq and Ganjoo 2017). Presence of secondary metabolites in different plant parts of wild pomegranate and high antioxidant activity is responsible for its health benefits and medicinal properties (Kaur et al 2018).…”
Section: Introductionmentioning
confidence: 99%